2009
DOI: 10.1016/j.jjcc.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Thrombo-occlusion of inferior vena cava filter in a patient with polycythemia vera

Abstract: This is a case of a thrombo-occlusion occurring below an inferior vena cava (IVC) filter inserted in a patient with polycythemia vera and deep vein thrombosis. The patient was a 48-year-old man with polycythemia vera and a chief complaint of swelling, redness, and bursting pain in his right leg. After admission, contrast-enhanced computed tomography scanning demonstrated a pulmonary artery thrombus and deep vein thrombosis. We inserted a Gunther tulip vena cava filter on day 1 for the prevention of pulmonary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In those cases, we should keep anticoagulant therapy, if possible, for preventing new PE or DVT deterioration. Numerous complications are associated with the long-term use of IVC filters (over 30 days), including migration, thrombosis, and IVC perforation [13][14][15][16][17][18][19][20][21]. However, in our small number of cases, we did not experience major filter-related troubles during long-term indwelling.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In those cases, we should keep anticoagulant therapy, if possible, for preventing new PE or DVT deterioration. Numerous complications are associated with the long-term use of IVC filters (over 30 days), including migration, thrombosis, and IVC perforation [13][14][15][16][17][18][19][20][21]. However, in our small number of cases, we did not experience major filter-related troubles during long-term indwelling.…”
Section: Discussionmentioning
confidence: 52%
“…IVC filters have been used for PE prophylaxis in patients with head injury, trauma, and pregnancy, and in preoperative DVT patients [9][10][11][12]. However, numerous complications are associated with the use of IVC filters, including migration, thrombosis, and IVC perforation, in patients with long-term use (over 30 days) [13][14][15][16][17][18][19][20][21]. Filter retrieval is recommended once the risk of PE is reduced and anticoagulant therapy is no longer contraindicated [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the biconical IVCF design also induces IVCF thrombosis because of the inverted conical design and the resultant flow dynamics (19). Reports have indicated that occlusion and/or the development of thrombi in the IVCF occurred in patients with polycythemia vera, heparin-induced thrombocytopenia, and patients without anticoagulants (20-22). Furthermore, there have been reports that occlusion and/or the development of a thrombus in the IVC occurred in a patient with hereditary protein C deficiency and APS, even without an indwelling IVCF (23-25).…”
Section: Discussionmentioning
confidence: 99%